A development project in good progress – Makerspaces in three compulsory schools - Pétursdóttir, Svava; Jónsdóttir, Svala; Hjartarson, Torfi; Jónsdóttir, Svanborg Rannveig; Kjartansdóttir, Skúlína Hlíf (Menntavísindasvið Háskóla Íslands, 2022)
This article presents a study on the views of teachers at the halfway point of a threeyear school development project to implement makerspaces in three compulsory schools in Reykjavík: Ingunnarskóli, Selásskóli, and Vesturbæjarskóli. The main emphasis in the project is on students’ agency, engaging learning environments, collaboration, independence, and creativity; it also includes using ICT and integration of school subjects. In this project the teachers at the schools have taken part in educamps involving workshops on different aspects of makerspace pedagogy and practice. The City of Reykjavík supports the project with grants, and a research team from the School of Education at the University of Iceland has from the onset provided the schools with professional advice and research results on the project’s progress.The first study on the project that was published in 2021, based on interviews with teachers and teacher focus groups, described the initial steps of the project and showed that various social issues influenced implementation. In this study we aimed to identify the teachers’ views towards the project – including their interest, efficacy, types of support, and hindrances – around the midpoint of the three-year project.Theoretical backgroundThe theoretical background builds on research and theories about educational change. We discuss the complex and interactive social and tangible elements that influence change, either by facilitating or impeding it. Personal and professional features, such as whether new ways of working align with teachers’ professional working theories, also have an impact.To understand the intricate developmental progress of the implementation, we use the model of social ecology of change, which describes how changes in education occur in steps, and how social systems that influence innovation need to change accordingly in an interactive way.MethodTwo of the schools serve student grades 1–7 (6–12-year-olds) and one serves grades 1–10 (6–16-year-olds). A survey was sent to all 80 ...